The role of ferroptosis in esophageal cancer - Zimin Wang; Sikai Wu; Chengchu Zhu; Jianfei Shen (Cancer Cell International, 2022)
Abstract Esophageal cancer is one of the most common cancers with high mortality rate around the world. Although the treatment strategy of this disease has made great progress, the prognosis of advanced patients is not ideal. Ferroptosis, a novel regulatory cell death model, that is different from traditional apoptosis and characterized by increased Fenton reaction mediated by intracellular free iron and lipid peroxidation of cell membrane. Ferroptosis has been proved to be closely linked to a variety of diseases, especially cancer. This review aims to summarize the core mechanism of ferroptosis in esophageal cancer, the regulation of ferroptosis signaling pathway and its current application. At the same time, we emphasize the potential and prospect of ferroptosis in the treatment of esophageal cancer. Collectively, targeting ferroptosis pathway may provide new insights into the diagnosis, treatment and prognosis of esophageal cancer.